Kinetics of spinodal decomposition, metastable ordering, and discontinuous precipitation in Cu‑15Ni‑8Sn - Hogg, J. M.; Vollhüter, Jan; Church, N. L.; Andersson, A. M.L.; Dejoie, C.; Collins, D. M.; Neumeier, Steffen; Stone, H. J. (Journal of Alloys and Compounds, 2025)
Cu‑15Ni‑8Sn (wt%) undergoes multiple concurrent phase transformations during ageing, which strongly influence its mechanical properties. Here, high-resolution synchrotron X-ray diffraction is utilised to study the microstructural changes that occur during ageing at 395 °C. Diffraction signals associated with spinodal decomposition, metastable ordering to form γ′‑L12 and γ″‑D022 precipitates, and discontinuous precipitation of γ‑D03 and δ‑D0a phases are identified and their temporal evolution monitored. Quantitative analyses of the diffraction data reveal that the characteristic wavelength of the spinodal microstructure exhibits a power‑law time dependence, consistent with the Lifshitz‑Slyozov‑Wagner (LSW) theory of particle coarsening. Precipitation of γ″ is observed to precede that of γ′, while γ is progressively replaced by δ in the later stages of ageing. The total volume fraction of discontinuous precipitation is well described by the Avrami model for nucleation and growth. Asymmetric diffraction peak profiles observed in the unaged condition are attributed to coherency strains arising from quenched‑in elemental clustering, as detected by atom probe tomography. Collectively, these findings offer insights into the interplay between spinodal decomposition, metastable ordering, and discontinuous precipitation in this alloy.
CRIS-Team Scopus Importer:2025-10-10
Keywords: Atom probe tomography; Copper alloy; Discontinuous precipitation; Phase transformation; Scanning electron microscopy; Spinodal decomposition; Synchrotron X-ray diffraction